Biomechanical characteristics of movement phases of snatch style in performace weightlifting - Ulareanu, M. V.; Potop, V.; Timnea, O. C. (Science, Movement & Health, 2013)
The purpose of this paper is to highlight the kinematic and dynamic characteristics of movement phases of snatch style in performance weightlifting. Methods and procedures. This scientific approach has led to a study conducted during the European Junior Weightlifting Championships, Bucharest, 2011, with a group of 7 athletes, finalists of 56 kg class. The methodology of research focused on video recording, conversion of video capture into AVI format and the video biomechanical analysis of weightlifters` performances by means of a specialized program named Physical ToolKit. Results. Each execution has shown the trajectories of the main joints involved in movement, highlighting the kinematic and dynamic characteristics of snatch style phases. The comparative analysis of the biomechanical indicators of movement phases in terms of beginning, extension, scoop, dip-under, catch and squat emphasize the duration of phases, the execution speed and the force to overcome the resistance of the barbell. Conclusions. The study results revealed the kinematic and dynamic characteristics of movement phases of the snatch style, especially the snatch, phases that had an influence on the performances achieved in competition.